Authentication of saffron spice accessions from its common substitutes via a multiplex approach of UV/VIS fingerprints and UPLC/MS using molecular networking and chemometrics. (15th January 2022) - Hegazi, Nesrine M.; Khattab, Amira R.; Frolov, Andrej; Wessjohann, Ludger A.; Farag, Mohamed A.
Highlights: Molecular network-based LC-MS/MS analysis of saffron and its inferior counterparts. 71 metabolites were annotated belonging to different classes. UPLC/MS dataset-based OPLS-DA analysis unveiled saffron originality and fraudulence. Modelling of UV/VIS spectral fingerprints supported the UPLC/MS results. Abstract: Saffron is a spice revered for its unique flavor and health attributes often subjected to fraudulence. In this study, molecular networking as a visualization tool for UPLC/MS dataset of saffron and its common substitutes i.e. safflower and calendula (n = 21) was employed for determining genuineness of saffron and detecting its common substitutes i.e. safflower and calendula. Saffron was abundant in flavonol- O -glycosides and crocetin esters versus richness of flavanones/chalcones glycosides in safflower and cinnamates/terpenes in calendula. OPLS-DA identified differences in UPLC/MS profiles of different saffron accessions where oxo-hydroxy-undecenoic acid- O -hexoside was posed as saffron authentication marker and aided in discrimination between Spanish saffron of high quality from its inferior grade i.e. Iranian saffron along with crocetin di- O -gentiobiosyl ester and kaempferol- O -sophoroside. Kaempferol- O -neohesperidoside and N, N, N, - p -coumaroyl spermidine were characteristic safflower metabolites, whereas, calendulaglycoside C and di- O -caffeoyl quinic acid were unique to calendula. UV/VIS fingerprint spectral regions of picrocrocin (230–260 nm) and crocin derivatives (400–470 nm) were posed as being discriminatory of saffron authenticity and suggestive it can replace UPLC/MS in saffrom quality determination.